Effects of School Selected Factors on the Implementation of the Re-Entry Policy in Public Secondary Schools in the Gatundu South Sub- County, Kiambu County, Kenya - Muli, Mary M.; Piliyesi, Elizabeth; Koros, Peter (Journal of Education and Practice, 2023)
Purpose: In 1994, Kenyan Ministry of Education established a policy that expectant students should remain in school until due to delivery. In 1996, the policy was revisited and National Guidelines for School Re-entry in Basic Education was formulated in 2020 whose goal was to provide and improve re-entry for learners who drop out of school. This research aimed to assess the effects of school selected factors on the implementation of the re-entry policy in public secondary schools in the Gatundu South Sub- County, Kiambu County, Kenya. The study was based on Equality of opportunity theory propounded by Mithaug. Methodology: The Convergent parallel mixed research that yielded both quantitative and qualitative data. To gather quantitative and qualitative data in this study, a cross-sectional survey and case study designs were applied. The target population was 421 derived from 268 class teachers, 30 principals, 60 mother-students, 60 parents/guardians and 3 MOE officials. The sample size was 93 participants. Purposive and simple random sampling were used to get 53 class teachers, 10 principals, 2 Ministry of Education officials, 15 mother-students and 13 parents/guardians. The study used content, face, construct and criterion validity. Reliability of research tools and the quantitative data analysis was done using SPSS VERSION 21. The Cronbach Alpha reliability coefficient test results were at 0.933, greater than 0.7 affirming an acceptable level of internal consistency. The data collection tools included: questionnaires, face to face interviews, document analysis and phone interviews. Hypothesis was tested using Pearson correlation and results indicated negative correlation between government initiatives towards the implementation of the re-entry policy and school completion rate. The quantitative findings were elaborated in frequencies, tables, rates, pie diagrams and charts while qualitative data thematically dissected and presented narrative form. The researcher sought permission from NACOSTI, The Catholic University of Eastern Africa, and the Kiambu county government as a mandatory pre-study requirement. The participants of the study were given the essential information and confidentiality guaranteed. Findings: According to the findings of the study, the vast majority of all respondents had verbally heard about the re-entry policy or from the media. The teachers' and parents' level of education was commendable because they were able to comprehend the policy if channels of educating were utilized. The study also found that the re-entry policy was not supported by the government. Unique contribution to theory, practice and policy: The study recommends accurate dropout records, leave applications, and follow-ups for girls, as well as comprehensive retraining for guidance and counseling teachers to address teenage pregnancy cases and support mother-students.